Development Of A Roadmap For Sustainable Research And Community Service As An Effort To Improve Quality - Kharisma, Fresha; Saputra, Irwan Adimas Ganda; Rahman, Muhammad Fajar Wahyudi; Fahmi, Moh Farih; Restikasari, Wenny; Akbar, Rasyidi Faiz (International Journal Business, Management and Innovation Review, 2025)
The Faculty of Economics and Business (FEB) has an important responsibility in developing economic and business knowledge and contributing to society and the business world. In an effort to increase its contribution, FEB continues to develop strategies that are relevant to its vision and mission. The development of a research and community service road map is an integral part of this strategy. The goal is to identify relevant and effective research and community service priorities. The problem-solving approach in developing a road map involves situation analysis, stakeholder engagement, priority identification, strategy development, and monitoring and evaluation. These steps help FEB develop a road map that is oriented towards solving problems, relevant to stakeholder needs, and able to provide significant contributions. The state of the art and innovation in road map development include an interdisciplinary approach, the use of digital technology, a focus on sustainability, active community involvement, and increased collaboration with industry. FEB can update its road map by integrating these aspects to ensure relevance, innovation, and significant impact in research and community service.